IAIN BONE PUBLIC RELATIONS MANAGEMENT IN PRESENTING INTERESTING INFORMATION ABOUT CAMPUS - Qudratullah; Rosniar; Ananta, Wilda (Jurnal Dakwah Tabligh, 2023)
This research aims to examine the Public Relations management of IAIN Bone in presenting interesting information about the campus so that it can attract prospective new students to continue their education at IAIN Bone. This research uses qualitative research with a field approach. The research results show that IAIN Bone’s public relations management presents interesting information about the campus through the POAC process, namely: First, planning is an absolute requirement for every management or administrative activity. Second, the organization at IAIN BONE provides information and division of tasks to the public relations staff regarding all activities/agendas that will be carried out every day by the public relations staff. Third, Actuating, namely the process planned by universities to gain sympathy from the community. The implementation carried out by public relations in presenting information is by following the information needs required by students. Fourth, Controlling (Evaluation) is carried out by IAIN Bone Public Relations, namely controlling insight from posts starting from the level of shares, likes, and comments that arise from each post made by public relations and then looking for solutions to problems that arise from these posts.